Determinan Penggunaan E-Wallet Generasi Milenial Muslim - Aisyah Aisyah; Yulfan Arif Nurohman; Rina Sari Qurniawati (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2022)
The development of information technology provides advances in the financial sector, especially digital payments. At this time digital payments have become a necessity to get some of the access offered to the public. The purpose of this study is to examine the factors that determine the millennial generation to use e-wallets. The variables tested include perceived usefulness, perceived ease of use, perceived risk and perceived security. Respondents in this study are the Muslim millennial generation in Solo Raya area. Based on the results of the data search, a sample of 108 respondents was obtained. The technique of selecting respondents using purposive sampling which provides certain criteria to the sample. The research method used is descriptive research with multiple linear analysis. Tests were carried out using SPSS software by testing the validity and reliability before carrying out multiple regression to prove the hypothesis. Based on the data obtained, it shows that the majority of respondents are dominated by women, while the majority of jobs are private employees. The results of the variable test show that perceived usefulness and perceived usefulness have a positive influence on usage decisions for the Muslim millennial generation. The perceived risk and security variables do not affect the decision to use e-wallets.